Varieties in state capitalism and corporate innovation: evidence from an emerging economy - Lin, Y; Fu, X; Fu, X (Elsevier, 2021)
This paper contributes to the literature by examining the impact of different forms of state ownership on corporate innovation and the moderating effects of environmental, social, and governance (ESG) practices, economic policy uncertainty (EPU), and corruption in this ownership–innovation nexus. Building on both agency theory and institutional theory, we identify and divide the ultimate controlling shareholders into three types: central government, local government, and private shareholders. This study draws on data from 2629 listed firms in China between 2007 and 2015. Our results suggest that state-owned enterprises (SOEs) controlled by the central government show the strongest innovation performance in all scenarios. In addition, private firms outperform local SOEs in terms of patent quantity in both manufacturing and nonmanufacturing sectors and in high-economic-development regions, whereas local SOEs outperform their private peers with respect to patent quality, mainly in the manufacturing sector and high-economic-development regions. Such an ownership–innovation nexus is then found to be more pronounced for firms engaging in more ESG practices, during periods of higher EPU, and when less corruption is present. These findings demonstrate the value of diversity in state capitalism in guiding SOEs' heterogeneous innovation activities in emerging economies.